Does defibrillation testing influence outcomes after CRT-D implantation? A cause-of-death analysis from the DAI-PP study. (15th October 2016) - Perrin, Tilman; Mechulan, Alexis; Boveda, Serge; Beganton, Frankie; Defaye, Pascal; Sadoul, Nicolas; Piot, Olivier; Klug, Didier; Gras, Daniel; Perier, Marie-Cécile; Algalarrondo, Vincent; Bordachar, Pierre; et al.
Abstract: Background: Little data address the usefulness of defibrillation testing in patients with prolonged QRS duration, known for more advanced myocardial disease. We aimed to compare baseline characteristics and outcomes between patients who underwent defibrillation testing (DT +) and those who did not (DT −), immediately after the implantation of a cardiac resynchronization therapy with defibrillator (CRT-D). Methods: Data from all patients with ischemic or non-ischemic cardiomyopathy implanted in primary prevention with a CRT-D in 12 French centers were considered for analysis (2002–2012). Results: Out of the 1516 patients with DT information available, DT was performed in 958(63%) patients. Compared to DT − patients, DT + patients presented no significant differences in terms of age (65.1 ± 10.8 vs 64.7 ± 10.3 years, p = 0.45), LVEF (25%[20.0–30.0] vs 25%[20.5–30.0], p = 0.30), or etiologies of heart failure (ischemic: 49.6% vs 46.9%, p = 0.32). By contrast, DT + patients were less likely to present atrial fibrillation (25.3% vs 33.4%, p = 0.001), renal insufficiency (eGFR < 60 ml/min in 45.3% vs 51.7%, p = 0.04) and NYHA functional class ≥ III (68.9% vs 77.4%, p = 0.0006). All of the three perioperative deaths occurred in the DT + group and were related to DT itself. After a mean follow-up of 3.1 ± 2.1 years, the adjusted incidence of overall mortality was lower among DT + patients (adjusted HR 0.6, 95%CI 0.4–0.7, p < 0.0001). However, ICD-unresponsive sudden deaths remained very rare and no more frequently observed among DT − patients (p = 0.41). Conclusions: In our cohort, the higher (up to 40%) mortality at midterm among DT − patients is mainly reflecting their more severe cardiac disease, rather than a higher rate of ICD-unresponsive sudden death.